Creation of an Integrated System for Monitoring the Technical Condition of High-Quality Helicopter Units based on Fiber-Optic Technology - L. Lvov, Nikolay; S. Khabarov, Stanislav; Yu. Gavrikov, Mikhail (International Journal of Engineering and Technology, 2018)
This article discusses the problems of creating an integrated system for monitoring the technical condition of highly responsible helicopter units, and analyzed options for its creation. Fiber-optical technology is considered as a technology, on the basis of which it is possible to build an integrated system, since this technology makes it possible to measure various physical parameters such as vibration, deformation, temperature, acoustic emission and other parameters, and due to the miniature dimensions of the fiber-optic light guide. It can be built into the PCM design, which is a relevant factor due to the growth use of PCM in the design and manufacture of helicopters. The results of bench and flight tests of helicopter pilot and rotor blades with fasteners using fiber optic deformation sensors based on a Bragg fiber grille demonstrate the fundamental possibility of creating a system for monitoring the technical condition of helicopter rotors using fiber optic sensors .Also, there are examples of creating other elements of an integrated monitoring system based on the use of fiber-optic technology, such as a system for signaling the breakdown of air flow and flutter on the helicopter rotor blades, a system for measuring the weight and alignment of helicopter cargo and a system for monitoring the technical condition of the airframe.Â Â